The Genes Associated with Jasmonic Acid and Salicylic Acid Are Induced in Tropical Chili Pepper against Ralstonia solanacearum by Applying Arbuscular Mycorrhizal Fungi - Ambarwati, Erlina; Arwiyanto, Triwidodo; Widada, Jaka; Alam, Taufan; Andika, Ignatius Putra; Taryono, Taryono (MDPI, 2022)
Controlling soil-borne pathogens is a significant problem in agriculture. Arbuscular mycorrhizae have a potential role in controlling soil-borne pathogens by increasing plant phytohormone contents. However, the mechanism of resistance by mycorrhizae has not been fully elucidated, particularly against bacterial wilt disease in Solanaceae. This study examined the role of mycorrhizae in expressing genes involved in the signaling pathways mediated by jasmonic acid (JA) and salicylic acid (SA) in tropical chili pepper against the bacterium Ralstonia solanacearum. Seedlings from ten genotypes of chili pepper were inoculated with a consortium of five mycorrhizal species and/or inoculated with a mixture of nine isolates of R. solanacearum. The leaves of 10-week-old plants after the treatment were sampled for real-time polymerase chain reaction analysis. The results showed that the mycorrhizae strengthened the immune system of tropical chili pepper by increasing the relative gene expression levels of JA and SA in genotypes with high and low responsiveness to the mycorrhizae. The relative gene expression level of JA was related to the percentage colonization of mycorrhizae and the resistance of the tropical chili pepper genotypes to R. solanacearum. The relative gene expression level of SA was associated with the resistance of tropical chili pepper to R. solanacearum. © 2022 by the authors.